Problems in Non-formal Education: Equality Education Studies in Semarang City - Sunardi, Sunardi; Shofwan, Imam; ., Abdul Rahman; Gunarhadi, Gunarhadi (KnE Social Sciences, 2023)
The number of equality education programs has increased every year. One of the alternative education methods expected to reduce the dropout rate in Indonesia is non-formal education, one of which is equality education Package A, Package B, and Package C. There are some concerns surrounding equality education in Indonesia that make the implementation of equality education programs less effective. Evaluation is urgently needed for the improvement and development of the different programs so that the implementation of education in Indonesia is effective. This study aimed to discover the problems in implementing equality education programs in Semarang. This research used a descriptive qualitative approach. Data was collected through observations, interviews with 100 respondents, and documentation. Data analysis in the study used member-checking techniques. The results showed that there were five main problems in the implementation of equality education in Semarang City. Very low learning motivation, the level of awareness of the importance of education was low, infrastructure for practice was not adequate but theoretical learning has been fulfilled although not entirely satisfactory, many educators were not competent, the funding system was insufficient, and education management planning was not running well. The problems that occur must be followed up immediately so as not to cause new issues, so that the government, the community and stakeholders play an active role in improving the quality of education in Indonesia. Keywords: Problems, Non-formal Education, Equality Education, Semarang City